Reducer Efficiency and Its Measurement and Calculation - 张文祥; 陶升元 (Jixie chuandong)
A series of formulae for calculating the mechanical efficiency of reducer are developed and are proved by experiments.Upon this basis,an approach is proposed for estimating the mechanical efficiency of high-power reducers through simulation. This approach is found to be feasible,economical and reliable.